A study of the photocatalytic and photothermal properties of the quaternary rGO/TiO2/NiFe2O4/ZnO nanocomposite for water treatment - Ahmad Faiq Amin; Mahmood Rezaee Roknabadi; Mohammad Behdani; Mohammad Ranjbar (Discover Materials)
Abstract This study presents the synthesis and evaluation of a novel rGO/TiO2/NiFe2O4/ZnO nanocomposite for efficient solar steam generation (DSSG) and photocatalytic water purification. The nanocomposite, synthesized via a hydrothermal method, demonstrates exceptional photothermal performance, achieving a maximum evaporation rate of 3.53 kg m−2 h−1 and an evaporation efficiency of 89% under 3 sun illumination. The incorporation of reduced graphene oxide (rGO) facilitated effective heat localization at the water/air interface, minimizing heat loss to the bulk water, as confirmed by infrared imaging and temperature sensor data. Furthermore, the nanocomposite exhibited significant photocatalytic activity, effectively degrading methylene blue with a degradation efficiency of 97%. Water quality analysis confirmed the production of clean and drinkable water. The nanocomposite demonstrated excellent reusability and stability across multiple cycles. This cost-effective and efficient material holds significant potential for sustainable water purification and solar steam generation applications.